PET – A Problem on a Global Scale - Niewdana, Agnieszka; Kapkowski, Maciej (No Limits, 2021)
We deal with plastics on a daily basis. The reason for this is the wide range of their application. We surround ourselves with them in our homes and workplaces; they are used in many industries, but also in everyday life. Versatility and ease of use are their characteristic properties. Nowadays, the challenge is to be able to reuse the materials intended for disposal, i.e. to recycle them. Researchers from the Institute of Chemistry of the University at Silesia in Katowice are investigating these possibilities.